Patient satisfaction regarding biosecurity protocols in the face of COVID-19, Faculty of Dentistry, University of Costa Rica = Satisfacción de los pacientes respecto a los protocolos de bioseguridad ante el COVID-19, Facultad de Odontología, Universidad de Costa Rica - Gutiérrez Marín, Natalia 1975- (2022)
Biosecurity protocols are particularly important in dental practice. The aim of this research was to determine the level of patient satisfaction regarding biosecurity protocols used in the School of Dentistry of the University of Costa Rica, to avoid COVID-19 infections during dental care. A survey was sent by email to all patients who received dental consultations at the School of Dentistry between April and September 2021. They were asked about sociodemographic variables (sex, age range, approved educational level, and place of origin), as well as whether they considered safe the protocols used during the dental consultation to avoid COVID-19 infections. Descriptive statistics were performed proving the absolute and relative frequency of the socio-demographic variables and the satisfaction of patients with the protocols used. A Chi-square test was used to determine if there was a difference in patient satisfaction with biosecurity protocols to avoid COVID-19 infections during dental care and sociodemographic variables. 95.9% of the respondents considered the biosafety protocols used to be safe and there was no statistically significant difference between patient satisfaction with the protocols and sociodemographic variables. A large majority of patients who come to the UCR School of Dentistry are satisfied with the biosecurity protocols used to avoid COVID-19 infections during dental care.
Los protocolos de bioseguridad son muy importante en la consulta odontológica. El objetivo de esta investigación fue conocer el nivel de satisfacción de los pacientes respecto a los protocolos de bioseguridad utilizados en la Facultad de Odontología para evitar los contagios por COVID-19 durante la atención dental. Se envió una encuesta por medio del correo electrónico a todos los pacientes que recibieron consulta dental en la Facultad de Odontología entre abril y setiembre del 2021. Se les consultó sobre variables sociodemográficas (sexo, rango de edad, nivel educativo aprobado y lugar de procedencia), así como si consideraban seguros los protocolos empleados durante la consulta dental para evitar los contagios por COVID-19. Se realizó estadística descriptiva estableciendo la frecuencia absoluta y relativa de las variables sociodemográficas y la satisfacción de los pacientes con los protocolos empleados en la Facultad. Se utilizó la prueba de chi cuadrado para determinar si existía diferencia en la satisfacción de los pacientes respecto a los protocolos de bioseguridad para evitar los contagios por COVID-19 durante la atención dental y las variables sociodemográficos. El 95.9% de los encuestados consideró seguros los protocolos de bioseguridad empleados y no hubo diferencia estadísticamente significativa entre la satisfacción de los pacientes con los protocolos y las variables sociodemográficas. Una gran mayoría de los pacientes que acuden a la Facultad de Odontología UCR están satisfechos con los protocolos de bioseguridad empleados para evitar los contagios por COVID-19 durante la atención dental.
En revista Odóvtos, vol. 24, no. 3 (septiembre-diciembre 2022)
Descripción basada en el contenido visto el 05 de diciembre, 2024
También disponible en formato HTML y EPUB